Molecular Epidemiology of Tungro Viruses in East Malaysia and Development of Serological Detection Tools for Diagnosis of Rice Tungro Disease - Yee, Siew Fung (Universiti Malaysia Sarawak (UNIMAS), 2019)
Malaysia aspires to be a rice self-sufficient nation as rice is the main food staple for her citizens. Thus, a rice disease outbreak can cause major losses for the rice granaries in the country. One of the viral rice diseases of concern in Malaysia is the rice tungro disease (RTD). RTD is caused by two viruses, namely the Rice tungro bacilliform virus (RTBV) and Rice tungro spherical virus (RTSV). The disease was detected in West Malaysia and Sabah in East Malaysia since the early twentieth century, and only recently in Sarawak in East Malaysia. RTD is very well-studied in West Malaysia, where the nucleotide sequences of both tungro viruses isolated from West Malaysia were published. In contrast, relatively little is known of RTD and the tungro viruses circulating in East Malaysia. Therefore, the aims of this study were to characterise the nucleotide sequences of tungro viruses isolated from East Malaysia and develop a RTD diagnostic method using in-house generated reagents such as sera and antigens in the form of recombinant proteins. The sequences of coat protein 1 (CP1), CP2 and CP3 of RTSV, and the open reading frame 1 (ORF1), ORF2, ORF3 (CP gene) and ORF4 of RTBV isolated from East Malaysia were characterized and compared with sequences of other published isolates by phylogenetic analysis. The identities and nucleotide sequences of fourteen RTBV and five RTSV isolates from East Malaysia determined from this study could be the first record of tungro viruses from East Malaysia. Then, recombinant proteins were generated by cloning and expressing CP genes of RTSV and RTBV isolated from Sabah using the SUMO fusion expression system. The tungro isolates selected for cloning and protein expression had high similarities in the nucleotide and deduced amino acid sequences with all tungro isolates from East Malaysia. This was to ensure that the antibodies generated from the iv selected tungro isolates are able to detect both tungro viruses from East Malaysia. Lastly, in-house polyclonal antibodies against tungro viruses were generated using the purified tungro viruses and the produced recombinant proteins. Two recombinant proteins that have potential to replace purified tungro virions as antigens in antibody production, and a reactive anti-serum for use in serological detection of RTD were finally obtained from the cloning and expression of recombinant CP of tungro viruses and production of antibodies against tungro viruses, respectively.